Analysis of Education Funding Management in Improving the Quality of Schools through Training at SDS Santa Lusia Sei Rotan - Ester Justina Sinaga; Saloma Banjarnahor; Sukarman Purba; Eka Daryanto; Restu Restu (Budapest International Research and Critics University, 2023)
This article was written to analyze education financing management and school quality through training. The type of research used in this research is school action research (PTS) with descriptive quantitative data analysis. The number of samples in the study was 16 people (teachers and administrative staff). Data collection techniques through observation, questionnaires, and documentation. The results of research on education financing management obtained an overall average percentage of 86.00% in the good category. This indicates that the education financing management at SDS Santa Lucia has been carried out properly. The results of the discussion and categorization regarding the quality of the school as a whole from the indicators obtained an average percentage of 89.77% in the high category. So it can be concluded that the quality of education is based on indicators of facilities and infrastructure, educators/teachers and employees.